2022
DOI: 10.1161/strokeaha.122.040302
|View full text |Cite
|
Sign up to set email alerts
|

Novel Approach to Visualize Microglia Death and Proliferation After Intracerebral Hemorrhage in Mice

Abstract: Background: Microglia are important brain immune cells. However, it is difficult to differentiate microglia from monocyte-derived macrophages. To visualize microglia changes following intracerebral hemorrhage (ICH), we utilized a genetic knock-in mouse line, Tmem119 (transmembrane protein 119)-EGFP (enhanced green fluorescent protein), which expresses EGFP specifically in microglia. Methods: There were 2 parts in this study. First, autologous blood was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…In our previous study, 19 we were able to detect an enhanced green fluorescent signal in perihematomal microglia at day 3 and day 7 after experimental ICH in Tmem119-EGFP mice, along with an increased number of microglia. Similarly, microglia can be found with enhanced fluorescence signals after intracerebral thrombin injection.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…In our previous study, 19 we were able to detect an enhanced green fluorescent signal in perihematomal microglia at day 3 and day 7 after experimental ICH in Tmem119-EGFP mice, along with an increased number of microglia. Similarly, microglia can be found with enhanced fluorescence signals after intracerebral thrombin injection.…”
Section: Discussionmentioning
confidence: 74%
“…17 Previously, we have used the Tmem119-EFGP mice to demonstrate the microglia death after ICH by day 1 and proliferation by days 3 and 7 as a natural history of microglia response to ICH. 19 In this study, we focused on the changes of MDMs versus microglia and, in particular, their phagocytic activity, as well as their response to phagocyte depletion with clodronate liposomes and phagocytic enhancement by CD47 blocking antibody. With the microglia identified with gene editing, the MDMs population can subsequently be established with a generalized macrophage marker (such as F4/80).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Timeline of microglia and iron after hemorrhage stroke (A) and ischemic stroke (B). These timelines are based on the data from the male rat model of AIS and HS 95–98 . Iron deposition in hemorrhage stroke is more rapid than in ischemic stroke due to the release of iron by the dissolution of mass red blood cells.…”
Section: Iron Metabolism In Brain Diseasesmentioning
confidence: 99%
“…In our recent work, we found that low doses of the pexidartinib (sufficient to deplete microglia but not peripheral macrophages) fail to substantially alter disease course while high doses prevent disease. Moreover, staining of lesions using a TMEM119-GFP reporter revealed that a substantial fraction of IBA1(+) cells in CNS lesions do not express this microglia-specific marker [24, 30]. Defining the roles of individual phagocytic cell populations is important for developing immune-targeting strategies into therapies, as CNS microglia and peripheral macrophages have distinct pharmacological properties and targets.…”
Section: Introductionmentioning
confidence: 99%